First case report of hospital staff infestation with cat flea (Ctenocephalides felis) in Iran - Amini Rarani, Saeid; Azami, Mehdi; Kiani, Fatemeh; Kazeroni, Tahereh Basir (German Medical Science GMS Publishing House, 2023)
Background: Cat fleas () are the most common ectoparasites of domestic cats and dogs worldwide. They can parasitize humans in many regions of the globe. Hospital infestation with fleas has not been reported in Iran, and the number of reported cases in the world is very low. Case presentation: Here we report and describe a hospital infestation with cat fleas in a number of health-care service personnel and nurses, which led to the development of skin lesions and severe itching. Conclusion: Diagnosing the parasite, removing it, and good health and medical management lead to satisfactory outcomes.